1981
DOI: 10.1107/s056774088100215x
|View full text |Cite
|
Sign up to set email alerts
|

Stacking variants of MnP4: preparation and structure of 6-MnP4

Abstract: Two new polymorphs of MnP 4 were prepared by reaction of the elemental components in a tin flux or by chemical transport in the presence of iodine. They can be considered as stacking variants (2-MnP4 and 6-MnP4) of a previously reported modification of this composition which is now called 8-MnP 4. The structure of 6-MnP 4 was determined from sin_gle-crystal counter data. It is triclinic, space group P1, with a = 16.347 (3) The Mn atoms with formal oxidation number +2 (d 5 system) are displaced from the centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 9 publications
0
7
0
3
Order By: Relevance
“…Similarly, powders of the binary alloys were used for the preparation of the ternary polyphosphides VNi 4 P 16 , NbNi 4 P 16 , and WNi 4 P 16 140. Three stacking variants of the binary manganese polyphosphide MnP 4 are known: 2‐MnP 4 ,56 6‐MnP 4 ,50 and 8‐MnP 4 49. The missing stacking variant 4‐MnP 4 could only be prepared in form of a solid solution with chromium: Cr 1− x Mn x P 4 with x having values between 0.3 and 0.7.…”
Section: The Tin Fluxmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, powders of the binary alloys were used for the preparation of the ternary polyphosphides VNi 4 P 16 , NbNi 4 P 16 , and WNi 4 P 16 140. Three stacking variants of the binary manganese polyphosphide MnP 4 are known: 2‐MnP 4 ,56 6‐MnP 4 ,50 and 8‐MnP 4 49. The missing stacking variant 4‐MnP 4 could only be prepared in form of a solid solution with chromium: Cr 1− x Mn x P 4 with x having values between 0.3 and 0.7.…”
Section: The Tin Fluxmentioning
confidence: 99%
“…Examples for binary phosphides and polyphosphides prepared in liquid tin are given in Table 1. It should be mentioned that the compounds SiP (sphalerite type),47 p ‐SiP 2 (pyrite type),47 CrP 4 ,48 MoP 4 ,48 and one modification of MnP 4 49—subsequently called 8‐MnP 4 50—were first thought to be high‐pressure compounds, because they could not be obtained by direct reaction of the elemental components at normal pressure. Their preparation by using a tin flux (for references see Table 1) showed that they must be considered as ambient‐pressure compounds.…”
Section: The Tin Fluxmentioning
confidence: 99%
“…Beispiele für binäre Phosphide und Polyphosphide, die aus Zinnschmelzen erhalten wurden, sind in Tabelle 1 angeführt. Es sollte erwähnt werden, dass die Verbindungen SiP (Sphalerit‐Typ),47 p ‐SiP 2 (Pyrit‐Typ),47 CrP 4 ,48 MoP 4 48 und eine Modifikation von MnP 4 49 – später 8‐MnP 4 genannt50 – ursprünglich als Hochdruckphasen beschrieben wurden, weil sie durch direkte Reaktion bei normalem Druck nicht erhalten werden konnten. Mit ihrer Herstellung aus einer Zinnflux (Literaturangaben in Tabelle 1) wurde bewiesen, dass es sich nicht um Hochdruckverbindungen handelt.…”
Section: Zinn Als Flussmittelunclassified
“…There are two metalmetal distances observed in MnB 4 , 269.61 (7) pm and 320.33 (7) pm (Figure 3 C), which is in contrast to the equally spaced metal atoms in CrB 4 . Compared to diamagnetic MnP 4 , which has an oxidation state of Mn II , MnB 4 shows even shorter Mn-Mn distances (in MnP 4 , Mn-Mn distances are greater than 292.1 pm [18] ). The MnÀMn bond in [Mn 2 (CO) 10 ] is also longer (292.3 pm) than the one observed in MnB 4 .…”
mentioning
confidence: 96%